In silico–guided Design and Endonuclease-Based Functional Validation of sgRNAs Targeting ERBB2 Transmembrane and Kinase Domains - Gunsi, Via Susana; Dirgahyu, Anugrah Prima; Meitha, Karlia; Christianto, Antonius; Tan, Marselina Irasonia (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Erythroblastic oncogene B2 (ERBB2) overexpression promotes breast cancer progression through activation of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and mitogen-activated protein kinase (MAPK) signaling pathways. Although CRISPR–Cas9 enables precise gene disruption, sgRNA efficiency is strongly influenced by target sequence and structural features, necessitating careful in silico design and validation. This study aimed to design and evaluate sgRNAs targeting the transmembrane- and tyrosine kinase–encoding regions of ERBB2.METHODS: Candidate sgRNAs were selected using CHOPCHOP, CRISPOR, and CRISPR RGEN, followed by secondary structure analysis with RNAfold to assess folding stability and scaffold integrity. sgRNAs were synthesized via in vitro transcription and assembled with Cas9 protein to form ribonucleoprotein (RNP) complexes. In vitro endonuclease assays were performed using PCR-amplified ERBB2 fragments derived from SK-OV3 genomic DNA, corresponding to exon 22 (523 bp) and exon 25 (933 bp). sgRNAs targeting eIF4E1 served as positive controls.RESULTS: Two sgRNAs meeting all in silico criteria were selected. Secondary structure prediction confirmed that both sgRNAs possessed essential structural elements required for Cas9 interaction including the repeat–anti-repeat region and three stem–loop structures. In vitro endonuclease assays demonstrated that the sgRNA targeting exon 22 of ERBB2 successfully cleaved its target DNA, producing fragments of 266 bp and 257 bp. Similar cleavage activity was observed in the two control sgRNAs, which generated fragments of 384 bp and 303 bp, and 486 bp and 201 bp, respectively. In contrast, the sgRNA targeting exon 25 of ERBB2 exhibited no detectable cleavage activity.CONCLUSION: The sgRNA targeting exon 22 of ERBB2 demonstrated effective DNA cleavage activity in vitro, whereas the sgRNA targeting exon 25 showed no endonuclease activity.KEYWORDS: CRISPR–Cas9, endonuclease, ERBB2, in vitro, breast cancer, RNP, sgRNA